2006
DOI: 10.1097/01.fpc.0000230420.05221.71
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of SLCO1B1 gene and the impact of *1b and *15 haplotypes on irinotecan disposition in Asian cancer patients

Abstract: These findings suggest that (1) SLCO1B1 haplotypes may have a significant influence on the disposition of irinotecan and its metabolites in Asian cancer patients, and (2) patients with SLCO1B1*15 haplotype may be susceptible to increased sensitivity to irinotecan, which may manifest itself either by increased efficacy or toxicity or both owing to the increased exposure levels to 7-ethyl-10-hydroxycamptothecin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 36 publications
5
53
0
1
Order By: Relevance
“…The clinical relevance of these findings was subsequently validated by comparing the pharmacokinetics and toxicity profiles in patients receiving irinotecan therapy (42,43). Patients with the OATP1B1*15 genotype showed increased systemic exposure and toxicities of SN-38 compared to those with the wild-type OATP1B1 (42,43). Similar findings have been reported with patients treated with methotrexate.…”
Section: Impact Of Oatp Polymorphisms On the Phar Macokinetics Of Antsupporting
confidence: 66%
See 1 more Smart Citation
“…The clinical relevance of these findings was subsequently validated by comparing the pharmacokinetics and toxicity profiles in patients receiving irinotecan therapy (42,43). Patients with the OATP1B1*15 genotype showed increased systemic exposure and toxicities of SN-38 compared to those with the wild-type OATP1B1 (42,43). Similar findings have been reported with patients treated with methotrexate.…”
Section: Impact Of Oatp Polymorphisms On the Phar Macokinetics Of Antsupporting
confidence: 66%
“…Compared to the wild-type OATP1B1 (OATP1B1*1a), the OATP1B1*15 displayed reduced uptake of SN-38 (an active metabolite of irinotecan), when tested in in vitro cell line models stably expressing OATP1B1 variant proteins (25). The clinical relevance of these findings was subsequently validated by comparing the pharmacokinetics and toxicity profiles in patients receiving irinotecan therapy (42,43). Patients with the OATP1B1*15 genotype showed increased systemic exposure and toxicities of SN-38 compared to those with the wild-type OATP1B1 (42,43).…”
Section: Impact Of Oatp Polymorphisms On the Phar Macokinetics Of Antmentioning
confidence: 99%
“…For example, some single-nucleotide polymorphisms of the genes encoding OATP, BCRP, and MRP2 have been associated with alterations in the pharmacokinetic profiles of statins (Niemi et al, 2006;Xiang et al, 2006;Hua et al, 2012;Konig et al, 2013). The increased expression of OATP and decreased expression of MRP2 may also alter pharmacokinetic parameters and disposition in patients with diabetes (Jung et al, 2001;Kast et al, 2002;Hasegawa et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we showed that SN-38 is a substrate of hepatic uptake transporter organic anion transporting protein (OATP)1B1 (Nozawa et al, 2005). Also, a genetic variant of OATP1B1 with reduced transport activity is associated with increased incidence of life-threatening toxicities resulting from increased systemic exposure to SN-38 (Xiang et al, 2006). Accordingly, both drug transporters and drug-metabolizing enzymes likely contribute to the pharmacologic and toxicologic actions of Another OATP family member, OATP2B1, is expressed in several tissues, including the liver and intestine (Tamai et al, 2000).…”
Section: Introductionmentioning
confidence: 99%